The Impact of a Modern Coffeeshops on Social Behavior and Cultural Dynamics: A Case Study of Unaizah' Coffeeshops - Kurniawan Arif Maspul; Fawaz Ali Almalki (CV. Ulil Albab Corp, 2023)
This study examines the impact of modern coffeeshops on social behavior and cultural dynamics in Unaizah. The opening of the coffeeshops has introduced a new gathering style, influencing the adoption of a contemporary lifestyle, particularly among the youth population. However, this transformation also raises questions about its implications for Unaizah's cultural identity and traditional values. Applying social influence theory and the concept of cultural adaptation, this research explores the underlying motivations and processes driving this social change. While tensions may arise between tradition and modernity, the fusion of old and new elements in the coffeehouse’s design presents an opportunity for preserving Unaizah's heritage while embracing contemporary influences. The study recommends further research to gain a comprehensive understanding of this social transformation and its long-term effects. Practical implications are highlighted to assist policymakers, community leaders, and coffeeshops owners in navigating the challenges and harnessing the benefits of this cultural shift. Moreover, by fostering dialogue and understanding, Unaizah can achieve a harmonious coexistence that balances tradition and modernity, ensuring a sustainable cultural landscape.